Universal-Diverse Orientation Promotes Congruent Ethnic and National Identities: A Preliminary Research Note: [Universal-Diverse Orientation Menguatkan Keselarasan Identitas Suku Bangsa dan Nasional: Catatan Penelitian Preliminer] - Burhan, Omar Khalifa; Nauly, Meutia; Purba, Ridhoi Meilona; Sinulingga, Rahma F.; Irmawati (ANIMA Indonesian Psychological Journal, 2022)
The present study conceptualizes “Unity in Diversity” as a condition in which individuals’ ethnic and national identities are congruent. This condition is achievable by internalizing universal-diverse orientation. The authors provide support for this idea through a cross-sectional survey (N = 400), and observed a positive relationship between individuals’ ethnic and national identities among individuals with high universal-diverse orientation. Such a relationship was absent among individuals with low universal-diverse orientation. Based on the results, the authors recommend socializing universal-diverse orientation to promote a sense of “Unity in Diversity” among individuals within a multicultural society, such as that of Indonesia. Studi ini mengonseptualisasi “Bhinneka Tunggal Ika” sebagai kondisi ketika terdapat keselarasan identitas suku bangsa dan nasional seorang individu. Kondisi ini bisa dicapai melalui internalisasi universal-diverse orientation. Penulis menyediakan data yang mendukung konsep ini melalui survei cross-sectional (N = 400), dan menemukan hubungan positif antara identitas suku bangsa dan identitas nasional pada individu dengan universal-diverse orientation tinggi. Hubungan ini tidak ditemukan pada individu dengan universal-diverse orientation rendah. Berdasarkan temuan ini, penulis merekomendasikan upaya sosialisasi universal-diverse orientation untuk menguatkan rasa “Bhinneka Tunggal Ika” pada individu dalam masyarakat multikultur layaknya Indonesia.